Impact of Corporate Governance on Firm Performance: An Empirical Study on Different Sectors in Pakistan - Sadaf Akhtar (Research Journal of Psychology, 2025)
In this era of globalization, the business world requires an outstanding system of governance. Many large and listed companies are increasingly concerned about these issues. Practicing good corporate governance can attract investment, improve organizational performance, and reduce investor risk. It is important to carefully consider the factors may affect the relationship between corporate governance and profitability. The purpose of this thesis is to examine the impact of specific variables of corporate governance on profitability using 10years of data (2010-2019) from 22 listed companies on the Pakistan Stock Exchange. The results indicates a positive impact of board meetings, gender diversity and board size on stock returns and Tobin’s Q, while showing a negative impact of leverage, board composition and audit committee members on Tobin’s Q and Stock return.